Laryngeal carcinoma with hemorraghic varicella : a rare case report - Aditomo, Rano; Antono, Dwi (PERHATI-KL, 2023)
Background : Hemorrhagic varicella is a complication that usually occurs in patients with immune disorders or those on immunosuppressive therapy or hematologic malignancies such as leukemia. Purpose: This case report aimed to further examine the complications of a rarely found hemorrhagic varicella in neck head malignancies / laryngeal carcioma. Case report : This is a case report of laryngeal carcinoma with hemorrhagic varicella in a 44-year-old man. Examination of dermatological status revealed hemorrhagic, polymorphic vesicles, generalized pustular psoriasis, erosion and, crusting. Tzanck test of the scrapes of the base of lesion of the vesicles is helpful in establishing the diagnosis of varicella and discovered multinucleated giant cells (MGCs) and epithelial cells with acidophilic intranuclear inclusion bodies The patient died after 3 days of treatment in the isolation room. A previous study also reported cases of hemorrhagic varicella in a 3-year-old girl with the main complaint of pus-filled red spots throughout the body. A previous history of chickenpox was denied. The physical examination showed dark red, polymorphic lession, generalized pustular psoriasis, erosion and crusting. Hemorrhagic varicella in the head and neck malignancy is a very rare form of varicella. Clinical question: In patient with immunocompromised during chemotheraphy suffer from varicella, is it necessary to have a comprehensive diagnostic examination panel, and therapy? Review methods: Evidence-based literature search with keywords “immunocompromised” AND “Hemorrhagic varicella” was performed through Cochrane, PubMed and Medline database. Result : The literature search obtained 318 articles in PubMed, 11 articles in Medline,and none in Cochrane, which were relevant with the topic. Only 1 article screened with inclusion and exclusion criteria. A research was conducted by Elizabeth et al in Philipina (2011) on Pediatric Infectious Disease and Hematology-Oncology Services. Out of 26 immunocompromised patients who developed varicella during the study period, only 22 charts were available for review. Of these patients, 13 were male and 9 were female. The highest incidence occurred from 0 to 5 years old (41%). Twenty patients had an underlying malignancy in the form of leukemia (14%) and solid organ tumors (6%) including nasopharyngeal cancer. Diagnosis based on the characteristic generalized papulovesicular rashConclusion : This requires a comprehensive diagnostic panel test for the delivery of appropriate therapy and improved outcome.